Behavioral delays in seeking care among post-acute myocardial infarction women: a qualitative study following percutaneous coronary intervention - Vincenza Giordano; Caterina Mercuri; Silvio Simeone; Teresa Rea; Michele Virgolesi; Rita Nocerino; Rita Nocerino; Vincenzo Bosco; Assunta Guillari (Frontiers in Global Women's Health)
BackgroundCardiovascular diseases (CVD) remain the leading cause of mortality worldwide, with ischemic heart disease contributing significantly to female morbidity and mortality. Despite this, women often delay seeking medical help during acute myocardial infarction (AMI), leading to poorer outcomes compared to men.ObjectiveTo describe the early experiences of Italian women with AMI, focusing on behaviors that delay access to care.MethodsUsing a phenomenological approach, in-depth interviews were conducted with 22 women hospitalized in Campania, Italy, within five days of an AMI event and their Percutaneous Coronary Intervention (PCI), to capture vivid recollections of the experience. Thematic analysis was employed to identify key themes regarding risk behaviors and delays in care.ResultsFive key themes emerged: (1) vivid recollection of symptoms and experience, (2) lack of knowledge and risk perception of AMI, (3) decision-making process in seeking assistance, (4) influence of family and others on decision-making, and (5) post-AMI reflections on seeking medical care. Delays in seeking care stemmed from symptom misrecognition, social responsibilities, past healthcare experiences, and the role of family in decision-making, which either facilitated or hindered access to care.ConclusionThe findings highlight the need for targeted educational interventions that address barriers specific to women in recognizing and responding to AMI symptoms. Gender-specific training for healthcare professionals is essential to ensure timely and appropriate care for women.